Shaping the composition profiles in heteroepitaxial quantum dots: Interplay of thermodynamic and kinetic effects - Georgiou, Christodoulos; Leontiou, Theodoros; Kelires, Pantelis C. (My University, 2014)
Atomistic Monte Carlo simulations, coupling thermodynamic and kinetic effects, resolve a longstanding controversy regarding the origin of composition profiles in heteroepitaxial SiGe quantum dots. It is shown that profiles with cores rich in the unstrained (Si) component derive from near-equilibrium processes and intraisland diffusion. Profiles with cores rich in the strained (Ge) component are of nonequilibrium nature, i.e., they are strain driven but kinetically limited. They are shaped by the distribution of kinetic barriers of atomic diffusion in the islands. The diffusion pathways are clearly revealed for the first time. Geometrical kinetics play a minor role.
Keywords: Epitaxial growth; Germanium; Kinetic theory; Monte Carlo methods